Rest Pain and Movement‐Evoked Pain as Unique Constructs in Hip and Knee Replacements. Issue 2 (February 2016) - Sayers, Adrian; Wylde, Vikki; Lenguerrand, Erik; Beswick, Andrew D.; Gooberman‐Hill, Rachael; Pyke, Mark; Dieppe, Paul; Blom, Ashley W.
Abstract : Objective: There is limited information about the extent to which the association between preoperative and chronic postoperative pain is mediated via pain‐on‐movement or pain‐at‐rest. We explored these associations in patients undergoing total hip replacement (THR) and total knee replacement (TKR). Methods: A total of 322 and 316 patients receiving THR and TKR, respectively, were recruited into a single‐center UK cohort (Arthroplasty Pain Experience) study. Preoperative, acute postoperative, and 12‐month pain severity was measured using self‐reported pain instruments. The association between preoperative/acute pain and chronic postoperative pain was investigated using structural equation modeling (SEM). Results: Patients with high levels of preoperative pain were more likely to report chronic pain after THR (β = 0.195, P  = 0.02) and TKR (β = 0.749, P < 0.0001). Acute postoperative pain‐on‐movement was not associated with chronic pain after TKR or THR after adjusting for preoperative pain; however, acute pain‐at‐rest was associated with chronic pain after THR (β = 0.20, P < 0.0002) but not TKR after adjusting for preoperative pain. Analysis of pain‐at‐rest and pain‐on‐movement highlighted differences between THR and TKR patients. Chronic pain‐at‐rest after THR was weakly associated with pain‐at‐rest during the preoperative (β = 0.11, P  = 0.068) and acute postoperative period (β = 0.21, P < 0.0001). In contrast, chronic pain‐on‐movement after TKR was strongly associated with the severity of pain‐on‐movement during the preoperative period (β = 0.51, P  = 0.001). Conclusion: SEM illustrated the different patterns of association between measures of pain over time in patients undergoing THR and TKR for osteoarthritis. These findings highlight the importance of future work that explores the mechanisms underlying pain‐on‐movement and pain‐at‐rest.